Waste Tire Particles and Gamma Radiation as Modifiers of the Mechanical Properties of Concrete - Eduardo Sadot Herrera-Sosa; Gonzalo Martínez-Barrera; Carlos Barrera-Díaz; Epifanio Cruz-Zaragoza (Advances in Materials Science and Engineering)
In polymer reinforced concrete, the Young’s modulus of both polymers and cement matrix is responsible for the detrimental properties of the concrete, including compressive and tensile strength, as well as stiffness. A novel methodology for solving such problems is based on use of ionizing radiation, which has proven to be a good tool for improvement on physical and chemical properties of several materials including polymers, ceramics, and composites. In this work, particles of 0.85 mm and 2.80 mm obtained from waste tire were submitted at 250 kGy of gamma radiation in order to modify their physicochemical properties and then used as reinforcement in Portland cement concrete for improving mechanical properties. The results show diminution on mechanical properties in both kinds of concrete without (or with) irradiated tire particles with respect to plain concrete. Nevertheless such diminutions (from 2 to 16%) are compensated with the use of high concentration of waste tire particles (30%), which ensures that the concrete will not significantly increase the cost.